Adsorption and solid catalysed reaction between activated carbon impregnated with SnO2 and CO at ordinary temperature - Iyuke, Sunny E; Ahmadun, Fakhru'l-Razi (Elsevier, 2002)
We have used pressure swing adsorption (PSA) measurements to study the reaction of CO adsorbed from H 2/CO (75/25vol.%) onto an activated carbon-tin(IV) oxide (AC-SnO 2 ) catalyst to form gaseous CO 2 . Unimpregnated pure activated carbon was used for comparison. Our data fit well to Langmuir-Hinshelwood kinetics with a rate constant of 0.022s -1 and an equilibrium constant of 1.04, indicating first-order kinetics. We conclude that chemisorption takes place preferentially on the adsorbed O - sites produced during the thermal pre-treatment of the catalyst.